Addressing College Food Insecurity: An Assessment of Federal Legislation Before and During Coronavirus Disease-2019 - Laska, Melissa N.; Fleischhacker, Sheila; Petsoulis, Christina; Bruening, Meg; Stebleton, Michael J. (Journal of nutrition education and behavior, 2020)
Research conducted before coronavirus disease-2019 illustrated high rates of food insecurity among college students. The pandemic has likely increased student food insecurity because of factors like unemployment and closure of campus resources, and many students cannot access federal food assistance because of long-standing student restrictions. This perspective reviews federal legislation on college food insecurity introduced in the 116th legislative session (2019–2020) immediately before coronavirus disease-2019 in the US, as well as pandemic-related stimulus bills and their implications for future policies and practice. Food insecurity promises to become more pressing as colleges try to reopen and the country grapples with economic recovery.